(untitled) (Modern education and development, 2024)
Qualities of strength, their manifestation occurs as a result of the influence of the organism, it occurs on the basis of the qualities of mental, muscle, motor, vegetative, hormonal functions and other physiological systems of the organism. Derived from these, power qualities are a broader concept in scope than the simplified concept of “muscle power”. Muscle strength is a developmental component of every movement activity. It can have a qualitative description, depending on the speed of manifestation, external resistance and duration of work.